Media Pembelajaran Dalam Meningkatkan Prestasi Siswa Sekolah Dasar Berbantuan Produk Adobe Flash - Agusniati, Andi; Putera, Wahyudi; Rasyid, Abd; Rajamemang, Rajamemang; Baharuddin, H.A. (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research aims to how to provide learning media development with Adobe Flash multimedia assistance in improving the achievement of elementary school students with improved learning in class VI Inpres Elementary School Complex BTN Pemda Makassar. The problems faced are how the description, design, validity and level of effectiveness in the development of learning media to improve learning achievement assisted by Adobe Flash products for grade VI students of Inpres Elementary School Complex BTN Pemda Makassar. This type of research is research and development for learning purposes. The development procedure refers to the 4-D model of Thiagarajan and Semmel (1974) which is adapted to 3-D. The data analysis technique in this study is Single group with pretest-posttest. The subject of this research is a subject matter expert of 1 person. Data collection techniques using interview, questionnaire and test techniques. The data analysis technique used in this research is qualitative with the research method using a qualitative descriptive approach and descriptive statistical analysis which prioritises data that is quality, statistical, subjective, and phenomelogical to produce conclusions. The results of this study indicate that the learning media for elementary school students of Inpres Kompleks BTN Pemda Makassar assisted by Adobe Flash application is in the category of very valid and very practical, so it is feasible to use on improving student achievement in elementary schools with the value of each stage of defining (Define) with a total score of 85 with an average score of 4 valid and 5 very valid. Furthermore, the planning stage (Design) for the recapitulation of the results of the RPP validation, the total score was 24.7 with an average score of 5 very valid and for the recapitulation of the LKS results with a total score of 64 with an average score of 4 valid and 5 very valid. Then the development stage (Development) for validation of student activities with a total score of 74.8 with an average of 5 very valid. As well as student learning outcomes for the percentage of completeness of learning outcomes with a total score of 93% complete and 7% incomplete. The research findings show the suitability of the Adobe Flash application designed as a learning tool to improve student achievement.